PSYCHOLOGICAL DISTRESS AMONG ORTHOPEDIC PATIENTS AND THE ROLE OF SOCIAL SUPPORT (Contemporary Journal of Social Science Review, 2025)
Objectives: This study aimed to explore the prevalence of psychological distress (anxiety, depression, and stress) among orthopedic patients, assess the role of social support in mitigating distress, and identify key demographic and clinical factors associated with psychological distress.Methods: A cross-sectional study was conducted at orthopedic hospitals in Gujrat, Pakistan, from January 2021 to March 2021. A purposive sampling technique was used to recruit 250 orthopedic patients (90 males, 159 females) aged 18 to 89 years. Data were collected using the Psychological Distress Scale (PDS) to measure anxiety, depression, and stress, and the Social Support Scale (SSS) to assess perceived social support. Statistical analyses, including Pearson’s correlation and multiple linear regression, were performed using SPSS Version 24.Results: The study found a high prevalence of psychological distress among orthopedic patients. The mean scores for anxiety, depression, and stress were 32.78 (SD = 1.50), 19.22 (SD = 1.16), and 21.53 (SD = 1.24), respectively. Psychological distress was significantly higher in female patients and those with a history of multiple hospitalizations. Pearson correlation analysis showed a significant negative association between social support and psychological distress (r = -0.549, p< 0.01). Regression analysis revealed that social support explained 30.2% of the variance in anxiety, 17.7% in depression, and 22.1% in stress (p < 0.01), indicating its crucial role in reducing psychological distress. Older age and family history of orthopedic disease were also significant predictors of distress.Conclusion: Psychological distress is prevalent among orthopedic patients, with social support playing a crucial role in reducing its impact. These findings highlight the need for integrating mental health interventions into orthopedic care to improve patient well-being